Dinamika Kolaborasi Ekonomi dalam Implementasi Program TJSL di Sektor Pengelolaan Sampah Kota Bandung - Amara Citta Wibowo; Ely Sufianti (LPPM University 17 Agustus 1945 Samarinda, 2025)
This study discusses the dynamics of collaboration in the implementation of the Corporate Social and Environmental Responsibility (TJSL) Program in waste management in Bandung City. As the economic and cultural center of West Java, Bandung faces significant waste management challenges due to rapid population growth and increasing economic activity. TJSL emerges as an alternative solution involving collaboration among the government, companies, and communities. This research aims to analyze how such collaboration is implemented, identify existing obstacles, and provide recommendations to enhance program effectiveness. A qualitative descriptive method was employed, using data collection techniques such as in-depth interviews, observation, and document analysis. The analysis refers to the Collaborative Governance theory by Emerson, Nabatchi, and Balogh (2012), which consists of three key components: principled engagement, shared motivation, and capacity for joint action. The findings show that although collaboration has taken place through the TJSL Forum and initiatives like waste cart assistance, its implementation still faces several challenges, including limited community capacity, lack of transparency from companies, and suboptimal cross-sector coordination. Strengthening institutional capacity, enhancing technical capabilities, and encouraging more meaningful community involvement are essential for TJSL to contribute effectively to waste management and sustainable development in Bandung City.